Correlation between glass fiber suspension characteristics and physical of glass fiber felt: Role of beating time and speed. Issue 1 (June 2022) - Hu, Jian; Zhang, Junxiong; Han, Ruonan; Yang, Yong
As the most significant process in papermaking technology, beating process changes parameters of fibers as aspect ratio, flocculation characteristics, and physical properties. In this paper, the correlation between glass fiber suspension characteristics and physical properties of glass fiber felts is explored. The influence of beating time and speed on the physical properties of glass fiber suspension and felts is studied. The results show that beating degree and viscosity of glass fiber suspension reduce by the increased beating time and speed, which finally stabilizes at around 11.0°SR and 200 mPas, respectively. The homogenization of suspension and the decrease of aspect ratio increase the drainage resistance and settlement index. It also finds that uniformity of glass fiber felt is improved by beating progress and tensile strength of glass fiber felt reduces with the increase of beating speed. However, dispersing process can improve tensile strength and increase by 81.5% at the dispersing speed of 500 r/min for 2 min.